2011
DOI: 10.1007/s00170-011-3603-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical performance analysis of hybrid metal-foam/composite samples

Abstract: In this research work, a hybrid metal-foam/ composite sample with axisymmetric geometry has been manufactured: the sample is composed by a cylindrical core in metal foam and an outer layer in composite material, manufactured by filament-winding technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Recently, based on the multi-material concept, hybrid structures have been developed by combining the periodic open-cell aluminium foams [20][21][22][23][24][25] or Advanced Pore Morphology (APM) foam elements [26][27][28][29][30] with polymers in which the voids of an open-cell aluminium foams are completely infiltrated with a polymer. Results have demonstrated that the polymer lead to an enhancement of the compressive strength and energy absorption of the resulting hybrid structures compared to the conventional opencell aluminium foams.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, based on the multi-material concept, hybrid structures have been developed by combining the periodic open-cell aluminium foams [20][21][22][23][24][25] or Advanced Pore Morphology (APM) foam elements [26][27][28][29][30] with polymers in which the voids of an open-cell aluminium foams are completely infiltrated with a polymer. Results have demonstrated that the polymer lead to an enhancement of the compressive strength and energy absorption of the resulting hybrid structures compared to the conventional opencell aluminium foams.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that in this way it is possible to achieve desired functionality necessary to satisfy requirements of a specific application. Few works have been published in this field [11][12][13][14][15][16][17][18][19], developing and testing hybrid foams based on both metal open-cell structures [12][13][14][15] and closed-cell foams [16][17][18][19]. Herein, further research in this field is presented in which the hybrid foam specimens of different sizes, combining aluminium alloy open-cell foam and two different polymer types, were developed, fabricated, tested and mechanically characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Such a decision is in order to clearly evaluate the effect of the foam core on the impact behavior of the component. After a preliminary research on the energy absorption for each sample, the impact tests have been carried out using the clamping device of the above mentioned drop weight impact machine (Fig. .b).…”
Section: Experimental: Materials and Methodsmentioning
confidence: 99%